Everyone Matters: Eliminating Dehumanizing Practices in Physical Education. Issue 1 (4th December 2020) - Culp, Brian
Abstract : Recently, discussions regarding how to create a positive school climate where all can be successful has come to the forefront. Healthy schools support student learning, well-being, time, space to be active, and opportunities for social and emotional growth. However, a host of numerous trends suggest that the school climate is becoming increasingly hostile towards students who are from immigrant, LBGTQ, and ethnic minority groups. What is often seen as disrespectful behavior toward these students is in fact actions that can be more accurately defined as dehumanization. This article overviews the practice of dehumanization, the implications for learning, and introduces proactive strategies to promote the success of all students.